Prinsip-Prinsip Kristen dalam Manajemen Sekolah dan Dampaknya terhadap Kinerja Guru - Siama, Jeferson; Prawono, Yanwar (TEVUNAH: Jurnal Teologi dan Pendidikan Kristen, 2024)
The principles of love and justice, derived from Christian teachings, can be applied to various aspects of school management. Love can be manifested through ethical, caring, and individual-centered approaches in the educational environment, while justice can be implemented by ensuring fair and transparent management policies and practices. This study aims to explore the application of Christian values, particularly love and justice, in school management and its impact on teacher performance. A literature review method was employed to examine relevant research. The findings indicate that Christian principles, especially love and justice, have a significant positive impact on the school environment and teacher performance. The implementation of love creates a supportive environment, enhances teacher satisfaction, and strengthens their motivation and commitment to their work. On the other hand, the principle of justice ensures fair and transparent school management policies and practices, reducing conflict and promoting collaboration among school staff. In conclusion, this study emphasizes the importance of considering Christian values in school management as a crucial factor in improving teacher performance and success, as well as creating an educational environment that supports teacher professional growth and student achievement. The integration of Christian values in school management has the potential to strengthen the foundation for holistic and sustainable education.